2014
DOI: 10.1002/ijc.28814
|View full text |Cite
|
Sign up to set email alerts
|

Methylation epigenotypes and genetic features in colorectal laterally spreading tumors

Abstract: Aberrant DNA methylation plays an important role in genesis of colorectal cancer (CRC). Previously, we identified Group 1 and Group 2 methylation markers through genome-wide DNA methylation analysis, and classified CRC and protruded adenoma into three distinct clusters: high-, intermediate-and low-methylation epigenotypes. High-methylation epigenotype strongly correlated with BRAF mutations and these aberrations were involved in the serrated pathway, whereas intermediate-methylation epigenotype strongly correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(72 citation statements)
references
References 52 publications
5
67
0
Order By: Relevance
“…The 24 tumor samples in Cluster-A significantly correlated with the presence of KRAS mutation ( P = 1×10 -4 ), and proximal location ( P = 3×10 -6 ) (Figure 2A). To evaluate methylation epigenotype of this cluster by comparison with the previously established methylation epigenotypes of sporadic CRC [12, 28], their methylation status was examined with 45 sporadic CRC samples, including 15 high-, 15 intermediate-, and 15 low-methylation epigenotypes, which had been previously evaluated [12]. Hierarchical clustering analysis revealed that all 24 tumor samples in Cluster-A were clustered into intermediate-methylation epigenotype (Figure 2B).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The 24 tumor samples in Cluster-A significantly correlated with the presence of KRAS mutation ( P = 1×10 -4 ), and proximal location ( P = 3×10 -6 ) (Figure 2A). To evaluate methylation epigenotype of this cluster by comparison with the previously established methylation epigenotypes of sporadic CRC [12, 28], their methylation status was examined with 45 sporadic CRC samples, including 15 high-, 15 intermediate-, and 15 low-methylation epigenotypes, which had been previously evaluated [12]. Hierarchical clustering analysis revealed that all 24 tumor samples in Cluster-A were clustered into intermediate-methylation epigenotype (Figure 2B).…”
Section: Resultsmentioning
confidence: 96%
“…As detected in intermediate-methylation sporadic CRC [12, 28, 31], it suggested that methylation accumulation and KRAS -mutation(+) are mostly completed by the adenoma stage.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Although the molecular mechanism involved in the development of LSTs is not fully understood, several studies reported frequent detection of KRAS mutation and CIMP in LSTs [25,26]. A more recent study showed that LST-G is associated with KRAS mutation and the intermediate-methylation epigenotype, while LST-NG is characterized by catenin beta-1 (CTNNB1) mutation and a low-methylation epigenotype [27].…”
Section: Epigenetic Silencing Of Neurotensin Receptor 1 Is Associatedmentioning
confidence: 99%